Money for nothing and your chips for free?: the anatomy of the PC wage differential - Haisken-DeNew, John P.; Schmidt, Christoph M. (Discussion papers, 1999)
In this paper, the role of the computer at the workplace will be examined in determining the wage structure in Germany. Following Krueger (1993) and using the German Socio-Economic Panel (GSOEP), cross-sectional wage regression results from 1997 and panel results from 1984-1997 are presented. It is shown that the wage premium attributed to using a computer at work using cross-sectional results for 1997 is around 7%. Further it is shown that computer usage is very heterogeneous depending on which industry one works in. In cross-section, hypothesis tests show that several industries and almost all firm size categories exhibit very different wage differentials depending on computer usage at the workplace. As DiNardo/Pischke (1997) stress the need for panel data to control for unmeasured individual effects, we use GSOEP 1984-1997 panel data, where a random effects and fixed effects estimator were run in the wage estimation. We confirm the results that Entorf/Kramarz (1997) had for France, that in Germany the coefficient for computer usage at the workplace did NOT remain stable and although just barely significant, was reduced to mere 1% with individual fixed effects. We conclude that there are no computer usage wage differentials worth speaking of, once one controls adequately for unobserved individual heterogeneity.
Keywords: 1984-1997; Graue Literatur; Arbeitspapier